Keanekaragaman Jenis Dan Dominansi Mangrove Di Pesisir Pantai Desa Sehati Kecamatan Amahai, Kabupaten Maluku Tengah - PATRICIA SIPAHELUT; D WAKANO; D E SAHERTIAN (BIOSEL (Biology Science and Education): Jurnal Penelitian Science dan Pendidikan, 2019)
Geographically, Indonesia is in the tropics. This causes Indonesian waters to become increasingly rich in various types of marine biota which must be found in coastal waters. Coastal waters are places where various ecosystems with high organic productivity are found, one of which is mangrove. Mangroves are plants that live in coastal areas whose lives are always influenced by tidal currents. This study will explain how the diversity of mangroves and how the dominance of mangrove species on the coast of Sehati Village, Amahai District, Central Maluku Regency. This research was conducted to determine the species diversity and dominance of mangrove species. So that the results of this study show that in the coastal waters of Desa Sehati, Amahai Subdistrict, Central Maluku Regency, 5 mangrove species were found, namely Rhizophora mucronata, Bruguiera cylindrica, Bruguiera gymnorhiza, Sonneratia alba and Nypa fruticans which were members of 2 classes (Magnoliopsida and Liliopsida), 2 orders (Myrtales and Arecales), 3 families (Rhizophoraceae, Sonneratiaceae and Arecaceae), and 4 genera (Rhizophora, Bruguiera, Sonneratia and Nypa) with medium species diversity indexes and low species dominance. Key Words: Mangrove, Species Diversity, Species Dominance